Analisis Disiplin Kerja Karyawan Pada Favehotel PGC Cililitan - Hanifah Septika (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the extent to which FaveHotel PGC Cililitan, in creating and enforcing work discipline for employees and agencies, in addition to knowing what steps need to be taken by FaveHotel PGC Cililitan in enforcing work discipline. In this case the researcher used a research design using a qualitative approach method with a purposive sampling technique. And data analysis methods using data reduction, data presentation, drawing conclusions and verification.